Competition Policies for the Telecommunications Industry in Korea - Nam, Il Chong (Deregulation and Interdependence in the Asia-Pacific Region, 2000)
Recently, real and artificial barriers to international transactions have fallen sharply, causing a rise in the overall volume of international trade. East Asia has been particularly affected by the economic stresses and gains derived from deregulation. Deregulation and Interdependence in the Asia-Pacific Region explores the broadly similar experiences of certain economies in the region—China, Hong Kong, Japan, Korea—in dealing with the potentially volatile process of deregulation, and examines the East Asian response to a rapidly transforming economic environment.